2010
DOI: 10.1590/s0102-695x2010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical, phytochemical and biological screening of Plinia cauliflora (DC.) Kausel, Myrtaceae, leaves

Abstract: RESUMO: "Rastreamento histoquímico, fitoquímico e biológico de folhas de Plinia cauliflora (DC.) Kausel (Myrtaceae)". No presente trabalho, foram investigadas a composição química e atividades biológicas de extratos brutos obtidos com etanol 50%, etanol 70%, acetona:água (7:3; v/v) e clorofórmio das folhas de Plinia cauliflora (DC.) Kausel, Myrtaceae, uma árvore nativa de várias regiões do Brasil. Os rastreamentos histoquímico e fitoquímico foram feitos de acordo com reações de caracterização e cromatografia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Keszei et al (2008) stated that the leaves of Myrtaceae species have high concentrations of terpenes and that these compounds show substantial qualitative and quantitative variations between each taxon, population and individual. Other phytochemical studies of Myrtaceae leaves have identifi ed sesquiterpenes, triterpenes, fl avonoids and alkaloids in Calycorectes psidiifl orus (Domingues et al 2010); fl avonoids, tannins and phenols in Plinia caulifl ora (Souza-Moreira et al 2010); and fl avonoids in Baeckea frutescens (Kamiya & Satake 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Keszei et al (2008) stated that the leaves of Myrtaceae species have high concentrations of terpenes and that these compounds show substantial qualitative and quantitative variations between each taxon, population and individual. Other phytochemical studies of Myrtaceae leaves have identifi ed sesquiterpenes, triterpenes, fl avonoids and alkaloids in Calycorectes psidiifl orus (Domingues et al 2010); fl avonoids, tannins and phenols in Plinia caulifl ora (Souza-Moreira et al 2010); and fl avonoids in Baeckea frutescens (Kamiya & Satake 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary phytochemical study of the ethanolic extract of the leaves confirmed the presence of hydrolysable tannins and flavonoids. Biological assays detected antioxidant (94.8% of radical scavenging capacity of 2,2-diphenyl-1-picryl-hydrazyl—DPPH) and antimicrobial activities, especially antifungal activity of the 70% ethanolic extract of the leaves against Candida albicans , Candida parapsilosis and Candida tropicalis (MIC of 625 µg/mL) [5]. It is well-known that Candida species under predisposing conditions can cause a range of infections from oral thrush and vaginitis, affecting the superficial mucosa, to candidaemia and systemic candidiasis in patients with compromised immunity [6].…”
Section: Introductionmentioning
confidence: 99%
“…In folk medicine, species of Plinia have been used in the treatment of stomach disorders, throat afflictions, and diabetes [ 19 ]. Biological properties of essential oil from P. trunciflora have not been reported, but leaf extract showed antioxidant and antimicrobial activities [ 20 ]. In a continuation of our systematic studies on pharmacologically active volatiles from Brazilian plants [ 21 , 22 ] we describe in this paper an evaluation of the chemical composition and antimicrobial activity of essential oils from leaves of E. uniflora and, for the first time, antimicrobial activity of essential oil from the leaves of P. trunciflora .…”
Section: Introductionmentioning
confidence: 99%